KOMUNIKASI ANTARPRIBADI ROLEPLAYER DI GRUP CHAT RAJASAWARDHANA - Milyawan, Artamevia Noverika (Solidaritas, 2025)
This research focuses on interpersonal communication in the Rajasawardhana Roleplayer chat group using WhatsApp social media with the aim of describing interpersonal communication in the Rajasawardhana Roleplayer chat group. This research uses an effectiveness study proposed by Joseph A. Devito which has 5 indicators including openness, empathy, support, positive feelings, and equality. The results of this study indicate that interpersonal communication in the Rajasawardhana chat group is openness between administrators and chat group members and fellow members, administrators provide information about changes in the flow of activities to members in order to maximize workmanship where administrators have empathy for members, members give each other encouragement when they will part with one another because the Rajasawardhana Roleplayer group has been disbanded, do not force chat group members who do not want to join the topic of conversation because they must prioritize their own comfort when interacting with others, old members and new members who have joined there is no difference and all are equal. The research method used is descriptive qualitative and uses purposive sampling to determine informants based on the length of time joining the Rajasawardhana Roleplayer chat group. Based on the results of the study, it can be concluded that interpersonal communication in the Rajasawardhana Roleplayer chat group has five aspects of effectiveness, namely openness, empathy, support, positive feelings, and equality so that members who are members of the Rajasawardhana Roleplayer chat group have a close relationship. Keywords: Interpersonal Communication, Roleplayer